Pedestrian Walking Characteristics through Angled Corridors: An Experimental Study. Issue 1 (January 2014) - Dias, Charitha; Ejtemai, Omid; Sarvi, Majid; Shiwakoti, Nirajan
Understanding pedestrian walking characteristics is important for the planning and design of mass gathering places for day-to-day activities as well as for emergency evacuations. The optimization of architectural designs and properly managing crowds at public buildings and the built environment is essential to ensure the safety and efficiency of crowd dynamics. Most previous empirical and theoretical studies highlight the behavior of a crowd as a whole system (macroscopic behavior) or interpersonal microscopic interactions within the crowd. A major gap in the knowledge is that no sufficient research has been carried out to examine solo walking characteristics, particularly when individual pedestrians interact with complex geometries such as turning. Whether the existing mathematical or simulation models can accurately reflect the characteristics related to solo human walking characteristics in these conditions is questionable. A series of experiments was conducted to understand the solo walking characteristics of individuals walking through angled corridors at different speeds. Initial results are discussed in detail. Results suggest that an individual tends to reduce speeds within a fixed region on the angled path and that the dimensions of this region are independent of turning angle but dependent on the individual's desired speed. These findings are important for the calibration of parameters or behavioral rules for microscopic pedestrian models.